An Uncommon Presentation of an Uncommon Colonic Neoplasia - Bodh, Vishal; Sharma, Rajesh; Sharma, Brij (Journal of Digestive Endoscopy, 2018)
Intussusception in adult is a rare clinical entity. The clinical presentation of adult intussusception is often nonspecific. Majority of the cases have been reported as chronic, consistent with partial obstruction. We report a case of a 53‑year‑old male, who presented with chronic diarrhea and vague abdominal discomfort. He was incidentally detected to have colocolic intussusception secondary to colonic lipoma during diagnostic colonoscopy.
Keywords: Contrast‑enhanced computed tomography; human immunodeficiency virus; IgA tissue transglutaminase